PEMANFAATAN SASTRA ANAK SEBAGAI MEDIA MITIGASI BENCANA - Else Liliani (LPPM UNY, 2010)
This article is about a study explaining: (1) kinds of the children literature that could be use as the media for disaster’s mitigation; (2) Compatibility and the accuracy of the child's literature for its prospective reader based on the cognitive development stage of the children; and (3) formulated utilization planning of the children literature to the disaster mitigation in Indonesian and literature learning. The children literature studied are twelve Indonesian children literatures, that consisted of the genre of fiction, poetry, the comic, and the non-fiction book (information). Respectively the genre was represented by three works. The children literature was taken through the purposive technique sampling. The data was analyzing by content analysis. The validity of the data was tested through the semantics validity and the reliability was tested by reading the text repeatedly. The results of the studied showed that: (1) The genre of the children literature that was found in this research was poetry, fiction, the comic and information (non-fiction). The elements that had the potential to use as the planting media for the mitigation of disaster were the theme and the message, the conflict, the characterization, the illustration, as well as the sound. ; (2) Based on the use of the point of view, the writing technique (the language) and the explanation of the problem, the poetry, fiction, and non-fiction (information) exact to be given to children age 7-11 years, whereas the comic was more exact given to the age 11 years – the adolescent; and (3) the disaster mitigation efforts could be carried out by understanding the contents of the text, gave the response to the problem of the disaster and the control as well as its prevention, or wrote the phenomenon of the natural or social disaster.